The effects of subcutaneous Tirzepatide on obesity and overweight: a systematic review and meta‐regression analysis of randomized controlled trials - Rohani, Pejman; Malekpour Alamdari, Nasser; Bagheri, Seyedeh Elaheh; Hekmatdoost, Azita; Sohouli, Mohammad Hassan (Frontiers in Endocrinology, 2023)
Background Despite the fact that obesity and overweight are serious major health problems worldwide, fighting against them is also considered a challenging issue. Several interventional studies have evaluated the potential weight-reduction effect of Tirzepatide. In order to obtain a better viewpoint from them, this study aimed to comprehensively investigate the effects of subcutaneous Tirzepatide on obesity and overweight. Methods Scopus, PubMed/Medline, Web of Science, Cochrane, and Embase databases were searched using standard keywords to identify all controlled trials investigating the weight loss effects of Tirzepatide. Pooled weighted mean difference and 95% confidence intervals were achieved by random-effects model analysis for the best estimation of outcomes. The statistical heterogeneity and publication bias were determined using the Cochran’s Q test and I2 statistics and using the funnel plot and Egger’s test, respectively. Results Twenty three treatments arm with 7062 participants’ were included in this systematic review and meta‐regression analysis. The pooled findings showed that Tirzepatide vs placebo significantly reduced body weight (weighted mean difference (WMD): -11.34 kg, 95% confidence interval (CI): -12.79 to -9.88, P< 0.001), body mass index (BMI) (WMD: -3.11 kg/m2, 95% CI: -4.36 to -1.86, P< 0.001), and waist circumference (WC) (WMD: -7.24 cm, 95% CI -10.12 to -4.36, P< 0.001). These reductions were even greater, especially with higher doses and duration of Tirzepatide. Conclusions Tirzepatide medication had significant effects on weight management with the reduction of body weight, BMI, and WC. Administration of Tirzepatide can be considered a therapeutic strategy for overweight or obese people.